(untitled) (Czech Journal of International Relations, 2000)
The author criticizes various concepts which define Central Europe. He argues that the discovery of this notion at the beginning of the 19th century was the result of failure to understand that differences between countries on the shores of the Atlantic and European inland countries did not have the character of classical differences between regions but that this was in fact lagging behind in the social and economic development within the framework of that section of European civilization which is based on the principles of Western Christianity (the Latin elements: Catholicism, Protestantism). Terms such as Western and Central Europe are not entirely suitable since they imply a geographical interpretation of a phenomenon which has a social and economic basis. That is why the Eastern border of the above-mentioned civilization of Western Christianity and the Western/Eastern border of a group of countries which we can label as “Western Europe” on the grounds of the level of their social and economic life is the Eastern border of Central Europe. The gradual expansion of “Western Europe” (by Germany, Scandinavia, etc.) constantly narrows down Central Europe until such time when it disappears entirely. It is at that stage that there could be a redefinition of this concept on a purely geographic and cultural historical basis. And while West European civilization is most attractive, it appears that its expansion will not come to a halt at the old border between Greek Orthodox and Latin Christianity. That is when Ukraine, Romania and others will take over the role of a bridgehead which is nowadays held by current Central Europe vis-à-vis “Western Europe”. The author includes Croatia, Slovenia, Hungary, Slovakia, the Czech Republic, and with some hesitation even Lithuania in a Central Europe defined in this way for the years 2000–2020. He sees their common interests in the following spheres: • maintaining a political and security system allowing also small states to survive • maintaining a peaceful, conflict-free coexistence of the nations in Central Europe • the prevention of internal ethnic conflicts within these states, • completion of social and economic transformation • accession to West European and Trans-Atlantic integration structures (NATO, EU) • increasing the interest shown by Western Europe in Central Europe • raising the prestige of the entire region • continued enlargement towards the East • interconnection of transport networks • maintaining access to worldwide raw material sources • removing barriers to their export • modernization of technologies • combating organized crime • protection against military threats • resisting possible German attempts at revanchism • joint solution of environmental problems, especially climatic changes It is an apparent paradox that small Central European nations should devote maximum efforts to ensure the disappearance of Central Europe as a political and social-economic entity, reflecting factual backwardness vis-à-vis Western Europe and, in an optimal sense, that it remains a cultural notion, or possibly manifesting some form of regional cooperation.